The effect of blood ketone concentration and exercise intensity on exogenous ketone oxidation rates in athletes - Dearlove, D. J.; Harrison, O. K.; Hodson, L.; Jefferson, A.; Clarke, K.; Cox, P. J. (Medicine & Science in Sports & Exercise, 2021)
Introduction: Exogenous ketones potentially provide an alternative, energetically advantageous fuel to power exercising skeletal muscle. However, there is limited evidence regarding their relative contribution to energy expenditure during exercise. Furthermore, the effect of blood ketone concentration and exercise intensity on exogenous ketone oxidation rates is unknown. Methods: Six athletes completed cycling ergometer exercise on three occasions within a single-blind, random-order controlled, crossover design study. Exercise duration was 60 min, consisting of 20-min intervals at 25%, 50%, and 75% maximal power output (WMax). Participants consumed (i) bitter flavored water (control), (ii) a low-dose ß-hydroxybutyrate (ßHB) ketone monoester (KME; 252 mg/kg BW, "low ketosis"), or (iii) a high-dose ßHB KME (752 mg·kg BW-1, "high ketosis"). The KME contained a 13C isotope label, allowing for the determination of whole-body exogenous ßHB oxidation rates through sampled respiratory gases. Results: Despite an approximate doubling of blood ßHB concentrations between low- and high-ketosis conditions (~2 mM vs ~4.4 mM), exogenous ßHB oxidation rates were similar at rest and throughout exercise. The contribution of exogenous ßHB oxidation to energy expenditure peaked during the 25% WMax exercise intensity but was relatively low (4.46% ± 2.71%). Delta efficiency during cycling exercise was significantly greater in the low-ketosis (25.9% ± 2.1%) versus control condition (24.1% ± 1.9%; P = 0.027). Conclusions: Regardless of exercise intensity, exogenous ßHB oxidation contributes minimally to energy expenditure and is not increased by elevating circulating concentrations greater than ~2 mM. Despite low exogenous ßHB oxidation rates, exercise efficiency was significantly improved when blood ßHB concentration was raised to ~2 mM.